Electrochemical study on the structure of PbO2 in mixed gel electrolytes during cycling by cyclic voltammetry. Issue 6 (21st December 2021) - Binh, Phan Thi; Van Anh, Nguyen Thi; Thuy, Mai Thi Thanh; Xuan, Mai Thi; Duyen, Nguyen The
Abstract: Pb/PbO2 electrodes are made by anodizing method from H2 SO4 solution (1.26 g/cm 3 ). The mixed gel electrolyte was prepared by mixing H2 SO4 (1.37 g/cm 3 ) with liquid glass (LG) in the presence of polyacrylamide (PAM), propylene glycol (PPG), and nano fumed silica (NFS). After finishing 150 cycles by cyclic voltammetry (CV) in different electrolytes at a scan rate of 100 mV/s, the structure of PbO2, including morphology and the content of elements, were analysed by scanning electron microscopy (SEM) and energy dispersion spectroscopy (EDS), respectively, as well as by CV diagrams. There was found a huge difference in both the grain size and surface structure of PbO2 electrodes. Among them, the morphology of PbO2 electrode after cycling in mixed gel electrolyte using PAM with NFS is similar to that obtaining from H2 SO4 solution (1.26 g/cm 3 ). The appearance of α‐ and β‐PbO2 forms depends on the combination of gelling agents. The existence of α‐PbO2 form was found only by using separate PAM or PAM with PPG leading to small discharge densities, while both α‐ and β‐PbO2 forms were clearly observed by combining PAM with NFS. The height of redox peak in this case is approximately the same as that in sulfuric acid solution.